Feeding postural behaviors and food geometric and material properties in bearded capuchin monkeys (Sapajus libidinosus). Issue 1 (27th February 2022) - Laird, Myra F.; Punjani, Zeenia; Oshay, Rachel R.; Wright, Barth W.; Fogaça, Mariana Dutra; van Casteren, Adam; Izar, Patrícia; Visalberghi, Elisabetta; Fragazy, Dorothy; Strait, David S.; Ross, Callum F.; Wright, Kristin A.
Abstract: Objectives: Foods that are geometrically and mechanically challenging to eat have been associated with specializations in feeding behavior and craniodental morphology across primates, and many of these foods are embedded, requiring a variety of positional behaviors during feeding. However, variation in positional behaviors in response to food properties is not well understood. Here, we examine differences in feeding postural behaviors across feeding events in relation to substrate and food geometric and material properties in a species of extractive foragers, bearded capuchins ( Sapajus libidinosus ). Methods and materials: We coded over 1400 co‐occurring postural and feeding behaviors, their durations, and relative sizes of substrate and food from videos recorded at Fazenda Boa Vista in Gilbués, Piauí, Brazil. Food material properties were measured from foods collected at the time of the video recordings. Results: Our results suggest that bearded capuchin feeding postures significantly differ across the feeding sequence, with substrate size, and between foods of high and low toughness and elastic modulus. Feeding postures were less variable for highly mechanically challenging foods. Food size also had a significant effect on postural behaviors. Large foods were more likely to be associated with suspended postures and small foods with sitting and squatting. Feeding postural behaviors were best explained by a combination of substrate and food variables. Conclusions: Our results indicate that food geometric and mechanical properties have a significant influence on feeding postural behaviors in bearded capuchins. We posit that feeding postural behaviors reflect a combination of substrate variables and food properties, and large, mechanically challenging foods have a limiting effect on postural variation.